Crystal violet stain as a selective stain for the assessment of mitotic figures in oral epithelial dysplasia and oral squamous cell carcinoma - Kiran B Jadhav; B R Ahmed Mujib; Nidhi Gupta (Wolters Kluwer Medknow Publications, 2012)
Background: Assessment of mitotic figures (MFs) is routinely practiced as prognostic indicator in oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC), but identification of MFs poses a problem in terms of staining characteristics. Aim: To evaluate effectiveness of crystal violet stain for staining of MFs and its comparison with hematoxylin and eosin (H and E) stain. Materials and Methods: Study sample includes archival tissues embedded in paraffin blocks diagnosed as OED (n = 30) and OSCC (n = 30). The control group comprised of tissue specimen from oral mucosa of healthy volunteers (n = 30). Two serial sections of each tissue specimen were stained separately with H and E stain and 1% crystal violet stain. The stained sections were observed under microscope for identification and counting of MFs. Data obtained was statistically analyzed by using the Man-Whitney U test. Results: A significant increase in number of MFs was observed in OED and OSCC in comparison with normal oral mucosa. There was a highly significant increase in number of MFs in crystal violet stained tissue sections when compared with H and E stain. Metaphase is the most commonly observed phase of mitosis in crystal violet stain when compared with H and E stain for all three groups. Conclusion: Crystal violet stain can be considered as selective stain for mitotic figures.